Розробка компонентів інформаційної системи управління багатоквартирним будинком - Медяник, М. Ю. (ХНУРЕ, 2024)
This project is dedicated to the development of components of an information system that enables users to report malfunctions in public utilities such as water, gas, etc. Such a system allows the user to create a request to request the repair of certain municipal facilities. The system has a three-tier architecture, in the form of an MSSQL DBMS in the data tier, a REST API implemented using ASP.NET on the business logic part, and an Angular application on the client side. The application will be accessible via a regular website through any browser.
Keywords: інформаційна система; управління багатоквартирним будинком; ASP.NET; Angular